Femoral artery pseudoaneurysm, an avoidable complication of femoral catheterization for hemodialysis - Sigdel, Mahesh Raj (Journal of Advances in Internal Medicine, 2013)
DOI: http://dx.doi.org/10.3126/jaim.v2i2.8779 Journal of Advances in Internal Medicine 2013;02(02):65-66